До характеристики об’єкта та предмета охорони праці поліцейських в Україні - Клочко, І. О.; Klochko, I. O. (Юридична наука. - 2020. - № 7(109). - С. 272-279, 2020)
Визначено, що об’єктом охорони праці є працівник поліції, а також середовище його професійної діяльності. Поліцейський як об’єкт охорони праці є: по-перше, людиною з визначеним рівнем стану здоров’я, який дозволяє йому виконувати професійні обов’язки поліцейського; по-друге, працівником, якому присвоєно спеціальне звання поліції та який виконує трудові функції, що відповідають займаній посаді, яку він обіймає на підставі наказу відповідної посадової особи. Середовище реалізації службово-трудових обов’язків поліцейського як об’єкт охорони праці визначається певними умовами реалізації таких обов’язків. В свою чергу предметом охорони праці поліцейських є сукупність нормативно-регульованих заходів, що утворюють систему забезпечення умов службово-трудової діяльності поліцейських, за яких буде збережено життя та здоров’я останніх. Зміст заходів, які складають предмет охорони праці поліцейського, знаходиться у безпосередній залежності від самих умов праці та завдань, які має виконати поліцейський.

Given the specifics of police work, an important task of the legislator in modern conditions is to create safe and appropriate conditions for their service. After all, the Constitution of Ukraine has enshrined that everyone, regardless of where they work, has the right to safe working conditions. In turn, ensuring the rights of police officers in the field of labor protection consists in the implementation of a set of various measures during the performance of police officers’ work and activities aimed at preserving life, health and their professional suitability. At the same time, ensuring the protection of police officers in Ukraine is a complex process that has its own object and subject. The article analyzes the scientific views of scientists who have studied the object and subject in general, and in the implementation of labor protection, in particular. It was stated that the object of labor protection is a police officer, as well as the environment of his professional activity. It is substantiated that the subject of police protection is a set of normative-regulatory measures that form a system of ensuring the conditions of service and labor activities of police officers, which will save the lives and health of the latter. It is concluded that the object of labor protection is a police officer, as well as the environment of his professional activity. A police officer as an object of labor protection is: first, a person with a certain level of health that allows him to perform the professional duties of a police officer; secondly, an employee who has been awarded a special police rank and who performs labor functions corresponding to the position he holds on the basis of an order of the relevant official. The environment for the performance of police duties as an object of labor protection is determined by certain conditions for the implementation of such responsibilities. In turn, the subject of police protection is a set of regulatory measures that form a system of ensuring the working conditions of police officers, which will save the lives and health of the latter. The content of measures that constitute the subject of labor protection of the police officer is directly dependent on the working conditions and tasks to be performed by the police officer.

Определено, что объектом охраны труда есть работник полиции, а также среда его профессиональной деятельности. Полицейский как объект охраны труда есть: во-первых, человек с определенным уровнем состояния здоровья, который позволяет ему выполнять профессиональные обязанности полицейского; во-вторых, работник, которому присвоено специальное звание полиции и который выполняет трудовые функции, соответствующие занимаемой должности, занимаемой на основании приказа соответствующего должностного лица. Среда реализации служебно-трудовых обязанностей полицейского как объекта охраны труда определяется определенными условиями реализации таких обязанностей. В свою очередь предметом охраны труда полицейских является совокупность нормативно регулируемых мер, образующих систему обеспечения условий служебно-трудовой деятельности полицейских, при которых будет сохранена жизнь и здоровье последних. Содержание мер, составляющих предмет охраны труда полицейского, находится в непосредственной зависимости от условий труда и задач, которые должен выполнить полицейский.
To the characteristics of the object and subjectofpolice protection in Ukraine
Клочко, І. О. До характеристики об’єкта та предмета охорони праці поліцейських в Україні / Клочко І. О. // Юридична наука. - 2020. - № 7(109). - С. 272-279. - DOI: https://doi.org/10.32844/10.32844/2222-5374-2020-109-7.35.
Клочко , І. О. (2020). ДО ХАРАКТЕРИСТИКИ ОБ’ЄКТА ТА ПРЕДМЕТА ОХОРОНИ ПРАЦІ ПОЛІЦЕЙСЬКИХ В УКРАЇНІ. Юридична наука, (7 (109), 272–279. https://doi.org/10.32844/10.32844/2222-5374-2020-109-7.35.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; поліцейські; police officers; полицейские; службово-трудова діяльність; official labor activity; служебно-трудовая деятельность; охорона праці; labor protection; охрана труда; об’єкт; предмет